I'm Unstoppable : “Academic resilience in overseas students outside Java and non-overseas students” - Pramudhita, Nubiyan Octa; Putri, Pradiptya Septyanti; Widhyastuti, Cahyaning (International Journal of Ethno-Sciences and Education Research, 2023)
Students are faced with many pressures and difficulties, both from the college where they study, such as academic demands to difficulties in doing assignments. Then pressure from outside, such as demands to share time with work and other reasons such as difficulty adjusting to a new place. This will certainly have an impact on the academic life of students, therefore they need academic resilience in order to survive, rise from adversity, to adapt positively to overcome all the difficulties they experience. This study aims to determine the description of academic resilience in overseas students from outside Java and non-overseas students in Bandung. This study uses quantitative methods with descriptive analysis, The sampling technique used was purposive sampling with a sample of 222 respondents consisting of overseas and non-overseas students in Bandung. Data collection using the academic resilience scale (32 valid items = 0.937) with analysis of research data using IBM SPSS Statistic 25 software for Windows. Based on the results of the processing, it was concluded that between overseas and non-overseas students there was no significant difference, namely, if rounded the results were 52% of respondents had a high level of academic resilience, then 48% of respondents had a low level of academic resilience.